NFC-Based Merit Point Attendance System (MPAZ) / Syafnidar Abdul Halim, Zulhaiman Mohd Nasir and Faridah Sappar - Abdul Halim, Syafnidar; Mohd Nasir, Zulhaiman; Sappar, Faridah (Faculty of Computer and Mathematical Sciences, 2021)
College hostels can be students’ prime accommodation, especially for those who live far away from the university. Number of rooms available at college hostels are limited. Due to the large number of students’ application for college hostels, the merit points-based on event attendances are used for the eligibility of college residency. The event attendance arrangement and merit points are generally done manually. Commonly organizers allot certain merit points to an event by distributing coupons and attendance sheets to participating students in the occasion. Thus, the merit points may be miscalculated. The tedious keying processes may be disputed for typing errors during data entry. In addition, due to the Covid-19 pandemic, the distribution of paper coupons and attendance sheets in crowded areas deters people from keeping a social distance of more than one meter and avoiding physical contact. The Malaysian Ministry of Health (MOH) recommends avoiding congested areas, confined spaces, and close conversation during the pandemic. Therefore, the aim of this project is to transform event attendance arrangement and traditional merit points collection into computerized, contactless, and paperless processes by implementing the Merit Point Attendance System (MPAZ). MPAZ is a near-field communication (NFC) based merit point attendance system to assist with college hostel residency qualification. The waterfall SDLC methodology is used for this project consisting of analysis, design, develop and test phases. The development of MPAZ includes several devices such as NFC reader (ACR122U), NFC cards, a server, and a wireless access point (AP). In conclusion, the college unit staff and students can utilize the MPAZ website to use and review the accumulated merit points and eligibility for college residency. Future works will include the development of mobile applications and the integration of biometric authentication in order to authenticate users, making the MPAZ system more secure.